A System for Monitoring and Reporting Excessive Passengers in Public Buses Case Study: Tanzania - Dina Machuve,, Kilavo Hassan, Anael Sam, (International Journal of Engineering and Computer Science, 2013)
In Tanzania, there has never been a technology for automatic monitoring and reporting excessive passengers in public buses. Despite having some stationing police at different locations for manual check up, the increase in prevalence of excessive passengers still persists. The finding of this study indicates that many deaths and injuries when accidents occur are caused by two major factors which are passengers overloading and not wearing seat belts. Many people are losing their lives and some are severely injured when accidents occur. The purpose of this work has been to develop a system for monitoring and reporting excessive passengers in public transport in Tanzania. It is based on Passive Infrared Sensor (PIR), Global Positioning System (GPS), and Global System for Mobile Communication (GSM) modem. The system is connected with SQL Server database which receives and stores all information. The system monitors the number of passengers boarding in public buses and reports to the respective authorities when a certain preset number is exceeded. This helps to control excessive passengers. Hence reduce the number of deaths and severe injuries when accidents occur, also helps eradicating bribery as through manual check the bus attendant can bribe the traffic police officer, communications to the traffic police officer will be improved as well as the bus owners, and improves the current system for manual check. Finally the passengers can find a sufficient level of mobility and satisfy their important needs for the efficient movement under safe and comfortable conditions. Keywords-Microcontroller, GSM Modem, PIR, GPS